Supercritical Carbon Dioxide Power Cycles with Oxy-Combustion Capture: Towards A New Improved Cycle Layout for Energy Production - Francisco García Weiss; Chakib Bouallou (Chemical Engineering Transactions)
The aim of this work is to introduce a new power cycle that could be a promising technology for increasing thermal efficiency, reducing cost of electricity while capturing nearly-all CO2 emissions. This cycle is based on existing supercritical CO2 oxy-fuel technologies, incorporating significant improvements in the process layout. The cycle is based on semi-closed loop recompression Brayton cycle that uses supercritical CO2 as the working fluid dramatically reducing energy losses compared to steam- and air-based traditional cycles. The oxy-combustion capture allows a full capture of carbon emissions through an air separation unit that provides pure oxygen to the system with cold energy integration of LNG. The proprietary feature of the new cycle is the recompression-based architecture, that increases the efficiency of the heat recuperative system. Promising results were obtained from first phase simulations: a 63 % LHV thermal efficiency for a 300 MW power plant, compared to a 59 % in the most efficient technology available on the market. First economic estimations show a 71.7 €/MWh LCOE, lowering the one from existing cycles. The balance between an increase in capital cost and a reduction in fuel demand was evaluated to ascertain the competitiveness of this advanced power cycle.